Clinical Practice Variation Among Adult Infectious Disease Physicians in the Management of Staphylococcus aureus Bacteremia. (2nd January 2019) - Liu, Catherine; Strnad, Luke; Beekmann, Susan E; Polgreen, Philip M; Chambers, Henry F
Abstract: Infectious disease management of Staphylococcus aureus bacteremia (SAB) was surveyed through the Emerging Infections Network. Although there were areas of consensus, we found substantial practice variation in diagnostic evaluation and management of adult patients with SAB. These findings highlight opportunities for further research and guidance to define best practices.